Highly Selective Fluorescent 4-(4-(Diethylamino)-2-Hydroxystyryl)-1-Methylpyridine Iodide and Nitrobenzofurazan Based Probe for Cysteine with Application in Living Cells. (11th February 2021) - Sun, Zhi-Bin; Hua, Yun; Gao, Meng-Jiao; Shang, Ya-jing; Kang, Yan-Fei
Abstract: Biological thiols, such as homocysteine, cysteine, and glutathione play key roles in physiological processes. However, due to the similarity of their structures and chemical properties, it has been a challenge to distinguish these compounds. In this work, a new fluorescent probe (E)-4-(4-(diethylamino)-2-((7-nitrobenzo[c][1, 2, 5]oxadiazol-4-yl)oxy) styryl)-1-methylpyridine iodide (Y-OH-NBD) is reported for the determination of cysteine. Based on the nucleophilic aromatic substitution and rearrangement cascade reaction, Y-OH-NBD was demonstrated to be a selective turn-on fluorescence probe for cysteine without interferences and probe consumption caused by high concentration of glutathione in phosphate buffer pH 7.4 containing 5% dimethyl sulfoxide. The Y-OH-NBD system determined cysteine with a response time of less than 5 min and a low limit of detection equal to 1.88 µM. Moreover, the probe showed low cytotoxicity and was conveniently applied to image intracellular cysteine in HeLa cells, indicating its significant potential biological applications.